A novel epigenetic AML1‐ETO/THAP10/miR‐383 mini‐circuitry contributes to t(8;21) leukaemogenesis. Issue 7 (24th May 2017) - Li, Yonghui; Ning, Qiaoyang; Shi, Jinlong; Chen, Yang; Jiang, Mengmeng; Gao, Li; Huang, Wenrong; Jing, Yu; Huang, Sai; Liu, Anqi; Hu, Zhirui; Liu, Daihong; et al.
Abstract: DNA methylation patterns are frequently deregulated in t(8;21) acute myeloid leukaemia (AML), but little is known of the mechanisms by which specific gene sets become aberrantly methylated. Here, we found that the promoter DNA methylation signature of t(8;21) + AML blasts differs from that of t(8;21) − AMLs. This study demonstrated that a novel hypermethylated zinc finger‐containing protein, THAP10, is a target gene and can be epigenetically suppressed by AML1‐ETO at the transcriptional level in t(8;21) AML. Our findings also show that THAP10 is a bona fide target of miR‐383 that can be epigenetically activated by the AML1‐ETO recruiting co‐activator p300. In this study, we demonstrated that epigenetic suppression of THAP10 is the mechanistic link between AML1‐ETO fusion proteins and tyrosine kinase cascades. In addition, we showed that THAP10 is a nuclear protein that inhibits myeloid proliferation and promotes differentiation both in vitro and in vivo . Altogether, our results revealed an unexpected and important epigenetic mini‐circuit of AML1‐ETO/THAP10/miR‐383 in t(8;21) AML, in which epigenetic suppression of THAP10 predicts a poor clinical outcome and represents a novel therapeutic target. Synopsis: AML1‐ETO can target and epigenetically suppress the novel gene THAP10 directly at the transcriptional level and indirectly at the translational one via miR‐383. This provides mechanistic insight on its role in t(8;21) AML leukemogenesis. AML1‐ETO protein localizes at an AML1‐binding site and triggers the epigenetic suppression of THAP10, which is associated with unfavorable outcome of t(8;21) AMLs. THAP10 is a bona fide target of miR‐383 which is transcriptionally induced by AML1‐ETO in t(8;21) AML. THAP10 is a nuclear protein that inhibits proliferation but promotes differentiation of t(8;21) AML cells. AML1‐ETO/miR‐383/THAP10 play a functional role in t(8;21) AML leukemogenesis in vivo . Abstract : AML1‐ETO can target and epigenetically suppress the novel gene THAP10 directly at the transcriptional level and indirectly at the translational one via miR‐383. This provides mechanistic insight on its role in t(8;21) AML leukemogenesis.